The Role of Digital Technology in Enhancing Public Service Efficiency in Indonesia - Yusuf, Mohammad Amil; Kusumawati, Andi; Irwansyah, Naila Syahirah; Haliah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study presents a systematic literature review on the role of digital technology in enhancing the efficiency of public service delivery in Indonesia. Drawing on 47 peer-reviewed articles published between 2019 and 2024, the review adopts a thematic synthesis approach guided by the PRISMA framework. Articles were identified through structured database searches, screened for relevance, and organized into three core themes: technology implementation, policy and institutional adaptation, and citizen engagement. The findings reveal that while digital infrastructure and system integration are essential enablers, successful implementation also depends on adaptive governance, coherent policy frameworks, and public trust. Although national initiatives have introduced centralized platforms and automation, regional governments continue to face structural, technical, and socio-demographic challenges. The review also highlights persistent gaps, including the lack of longitudinal evaluations, limited inter-agency collaboration, and underutilization of citizen feedback in policymaking. This study contributes to the literature on digital governance by proposing a conceptual framework that integrates technical, institutional, and societal dimensions of digital service reform. It also offers practical recommendations for aligning technological innovation with inclusive and responsive governance. Future research should examine the sustainability of sub-national reforms and explore strategies to improve digital equity and participatory policymaking.